The effect of N-acetylcysteine and working memory training on neural mechanisms of working memory and cue reactivity in regular cocaine users. (30th May 2019) - Schulte, Mieke H.J.; Kaag, Anne Marije; Boendermaker, Wouter J.; van den Brink, Wim; Goudriaan, Anna E.; Wiers, Reinout W.
Highlights: First study on effect of NAC on neural cue reactivity and cognitive functions in SUD. No treatment effect on cue induced craving or cue reactivity. No treatment effect on WM performance or associated activity in dACC or DLPFC. Limited effect of NAC on WM associated activity in VLPFC. Abstract: The current study investigated the combined effects of N-acetylcysteine and working memory (WM) training on behavioral and neural mechanisms of cue reactivity and WM in cocaine users in a randomized, double-blind design. Twenty-four of 38 cocaine-using men completed a 25-day treatment with either 2400 mg/day NAC or placebo. Both groups performed WM-training. During pre- and post-test lab-visits, neural mechanisms of cue reactivity and WM, and cue-induced craving and WM performance were assessed. Additionally, exploratory whole brain analyses were performed. Overall, the hypotheses were not confirmed, possibly due to small sample size, low WM-training adherence and/or ongoing substance use.